Implementation of Risk Management in Strategic Decision Making - Semman Ansyari (Journal of Scientific Interdisciplinary, 2024)
Risk management is an important aspect of an organization's decision-making strategy to manage uncertainty and identify opportunities in a complex business environment. This research aims to investigate the implementation of risk management in the context of strategic decision making, with a focus on the process of risk identification, risk evaluation, mitigation strategies, and their impact on achieving organizational goals. This research uses a qualitative approach with case studies as the main methodology. Data was collected through in-depth interviews with organizational leaders and analysis of documents related to risk management. The analysis steps include risk identification, risk evaluation using impact and probability assessment methods, as well as risk mitigation strategies applied in strategic decision making. The research results show that a comprehensive risk identification process provides a strong basis for designing effective risk management strategies. In-depth risk evaluation allows organizations to prioritize the most significant risks and develop appropriate mitigation actions. Implementation of risk mitigation strategies such as prevention, mitigation, transfer or retention of risk has contributed significantly to reducing the negative impact of risks faced by organizations. This research confirms that risk management is not only a tool to protect organizational value, but also a proactive approach that supports the achievement of long-term strategic goals. By implementing best practices in risk management, organizations can build a solid foundation for sustainable growth and success in a competitive and dynamic marketplace.